Editorial - Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
Welcome to the second issue of our thirteenth volume. With this publication we reach the sixteenth edition of our journal and continue moving forward towards meeting the challenges academic journals face nowadays to reach a target audience.